New host records and geographic distribution of species of Trichuris (Nematoda: Trichuriidae) in rodents from Argentina with an updated summary of records from America - Robles, María del Rosario (2014)
Species of Trichuris have a cosmopolitan distribution and parasitize a broad range of mammalian hosts. Although, the prevalence and intensity of this genus depends on many factors, the life cycles and characteristics of the environment have been the main aspect used to explain their geographical distribution. In this paper, we provide new host and geographical records for the species of Trichuris from Sigmodontinae rodents in Argentina. Moreover, we present comprehensive data about previous records of the genus from rodents in North and South America, and mainly in Argentina. A total of 563 specimens including in 25 species of rodents from 12 provinces and 43 localities from Northeast and Southern Argentina were sampled for Trichuris. Six species of Trichuris including 9 new hosts and 16 new geographical records were found. The prevalence of Trichuris in Misiones province is higher than in other geographical areas studied. This tropical-subtropical nematode group is recorded for the first time from the latitude 40º S. Nevertheless, more surveys are necessary to determine whether the scarcity of infections of Trichuris in regions of high latitude is due to the absence of sample effort or to environmental effects on the survival of infective stages.